2021
DOI: 10.22541/au.161184623.33282276/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An effective computational-screening strategy for simultaneously improving both catalytic activity and thermostability of α-L-rhamnosidase

Abstract: Catalytic efficiency and thermostability are the two most important characteristics of enzymes. However, it is always tough to improve both catalytic efficiency and thermostability of enzymes simultaneously. In the present study, a computational strategy with double-screening steps was proposed to simultaneously improve both catalysis efficiency and thermostability of enzymes; and a fungal α-L-rhamnosidase was used to validate the strategy. As the result, by molecular docking and sequence alignment analysis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Similarly, it was found that deletion of C‐terminus of arylacetonitrilase from Pseudomonas fluorescens EBC191 led to increased amide formation ability, but loss of enantioselectivity and significantly reduced enzyme activity (Kiziak et al, 2007). Although the stability‐activity trade‐offs were overcome by several groups in recent years (L. Li, Li, et al, 2021; S. F. Li, Xie, et al, 2021; Liu et al, 2019), the compromises among three or more enzyme properties have seldom been addressed to date.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it was found that deletion of C‐terminus of arylacetonitrilase from Pseudomonas fluorescens EBC191 led to increased amide formation ability, but loss of enantioselectivity and significantly reduced enzyme activity (Kiziak et al, 2007). Although the stability‐activity trade‐offs were overcome by several groups in recent years (L. Li, Li, et al, 2021; S. F. Li, Xie, et al, 2021; Liu et al, 2019), the compromises among three or more enzyme properties have seldom been addressed to date.…”
Section: Introductionmentioning
confidence: 99%